2021
DOI: 10.1186/s42490-020-00046-0
|View full text |Cite
|
Sign up to set email alerts
|

Electric field stimulation for tissue engineering applications

Abstract: Electric fields are involved in numerous physiological processes, including directional embryonic development and wound healing following injury. To study these processes in vitro and/or to harness electric field stimulation as a biophysical environmental cue for organised tissue engineering strategies various electric field stimulation systems have been developed. These systems are overall similar in design and have been shown to influence morphology, orientation, migration and phenotype of several different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 132 publications
(155 reference statements)
0
39
0
Order By: Relevance
“…It has been promised to deliver a stimulation of 100 V m −1 at a stimulation amplitude of 2.2 V (DC) (Mobini et al, 2016). In subsequent experimental studies, this field strength has been reported (sometimes without mentioning the applied voltage) (Mobini et al, 2017;Srirussamee et al, 2019) and has thus made it into literature reviews (Thrivikraman et al, 2018;Ryan et al, 2021). However, the theoretical model presented in Srirussamee et al (2021) has predicted a current density of 0.5 A/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been promised to deliver a stimulation of 100 V m −1 at a stimulation amplitude of 2.2 V (DC) (Mobini et al, 2016). In subsequent experimental studies, this field strength has been reported (sometimes without mentioning the applied voltage) (Mobini et al, 2017;Srirussamee et al, 2019) and has thus made it into literature reviews (Thrivikraman et al, 2018;Ryan et al, 2021). However, the theoretical model presented in Srirussamee et al (2021) has predicted a current density of 0.5 A/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation has been (re-)discovered as a tool for tissue engineering and regenerative medicine ( Balint et al, 2013 ; da Silva et al, 2020 ). In recent years, the effect of electrical stimulation on various cell lines and tissues has been studied in vitro ( Funk et al, 2009 ; Balint et al, 2013 ; Jahr et al, 2015 ; Thrivikraman et al, 2018 ; Chen et al, 2019 ; da Silva et al, 2020 ; Ryan et al, 2021 ). Nevertheless, no clear picture regarding optimal stimulation parameters (field strength, stimulation voltage/current) has been developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, cardiac pacing was introduced for cardiac resuscitation and technology advances, including cardiac pacemaker and defibrillator [75]. Other than cardiac devices, neuromuscular electrical stimulation (NMES) in sports medicine [76], transcutaneous nerve stimulation (TENS) for chronic pain [77], electroconvulsive therapy in psychiatric disorders [78,79], and deep brain stimulation in Parkinson's disease [80] are included as ES. There are three common modes of ES, which are direct current (DC), pulsed current (PC), and alternating current (AC).…”
Section: Common Modes Of Esmentioning
confidence: 99%